2013
DOI: 10.36076/ppj.2013/16/135
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pain Sensitivity on the Symptom Severity in Patients with Lumbar Spinal Stenosis

Abstract: Background: The symptom severity of back pain/leg pain is not correlated with the severity of degenerative changes and canal stenosis in lumbar stenosis. Considering the individual pain sensitivity might play an important role in pain perception, this discordance between the radiologic findings and clinical symptoms in degenerative lumbar stenosis might originate from the individual difference of pain sensitivity for back pain and/or leg pain. Objective: To determine the relationship among the clinical symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The addition of other symptomatic LSS psychometric scoring might be better to evaluate PSLD efficacy comprehensively and more objective. [ 2 57 58 59 60 61 62 ] A comparison between FE-PSLD and other management options is needed to define the best strategy. MRI changes comparison before and after PSLD during serial follow-up might be considered, even though Sirvanci et al .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of other symptomatic LSS psychometric scoring might be better to evaluate PSLD efficacy comprehensively and more objective. [ 2 57 58 59 60 61 62 ] A comparison between FE-PSLD and other management options is needed to define the best strategy. MRI changes comparison before and after PSLD during serial follow-up might be considered, even though Sirvanci et al .…”
Section: Discussionmentioning
confidence: 99%
“…24 Collectively, these results and ours implicate the possibility that severe to morbidly obese individuals may not be as receptive to analgesics or alternatively, may experience more severe spinal pathologies as compared with nonobese individuals. However, Kim et al 25 suggested that symptom severity may not be associated with severity of spinal pathology, and instead postulates that pain sensitivity may be the determining factor. Future studies aimed at pain thresholds among obese spinal patients are warranted to further clarify.…”
Section: Discussionmentioning
confidence: 99%